2002
DOI: 10.1002/cne.10214
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and maturation of zebrafish dorsal root and sympathetic ganglion neurons

Abstract: The trunk neural crest of vertebrate embryos gives rise to dorsal root ganglion (DRG) sensory neurons and autonomic sympathetic neurons, among other derivatives. We have examined the development of DRG and sympathetic neurons during development in the zebrafish. We found that sensory neurons differentiate rapidly and that their overt neuronal differentiation significantly precedes that of sympathetic neurons in the trunk. Sympathetic neurons in different regions differentiate at different times. The most rostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 37 publications
4
75
1
Order By: Relevance
“…1A,B, arrowheads) in wild-type embryos (Guo et al, 1999;Holzschuh et al, 2001;An et al, 2002) and a massive reduction of dbh-expressing cells in hands off mutant embryos (Fig. 1C,D,arrowheads).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…1A,B, arrowheads) in wild-type embryos (Guo et al, 1999;Holzschuh et al, 2001;An et al, 2002) and a massive reduction of dbh-expressing cells in hands off mutant embryos (Fig. 1C,D,arrowheads).…”
Section: Resultsmentioning
confidence: 88%
“…As sympathetic ganglion development in the rostral trunk is initiated just before 2 dpf, the hands off mutation provided the opportunity to investigate the role of hand2 in sympathetic ganglion development. We focus mainly on the initial stages of ganglion development in 2 and 3 dpf embryos, involving the specification and differentiation of sympathetic neurons (Guo et al, 1999;Holzschuh et al, 2001;An et al, 2002;Stewart et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the size of the DRGs continues to increase after their initial formation, even continuing postnatally to some extent (Namaka et al, 2001;An et al, 2002;Le Dourain et al, 2004). We identified a population of dividing cells from embryonic DRGS and observed that, as with trunk MNCs, they could differentiate into a population of neurons with properties similar to those of polymodal nociceptors.…”
Section: Discussionmentioning
confidence: 93%
“…It is known that after formation of the DRGs, these ganglia contain a population of dividing cells that continues to contribute to their maturation (Namaka et al, 2001;An et al, 2002). We therefore attempted to culture such a population from the DRGs of E14 mice, a time at which ganglion formation is nearly complete.…”
Section: Expression Of Cxcr4 By Cells From Embryonic Drgmentioning
confidence: 99%
“…16,39 Similar to the mammalian adrenal medulla, the chromaffin component of the interrenal organ is originated from the neural crest through sequential steps of differentiation. 45 In the zebrafish embryo, the trunk neural crest gives rise to dorsal root ganglion sensory neurons and autonomic sympathetic neurons. Sympathetic neurons from cervical ganglion subsequently express adrenergic differentiation markers dbh and tyrosine hydroxylase, and some migrate to the interrenal region to become endocrine chromaffin cells.…”
Section: Molecular Interplays Within Interrenal Primordiummentioning
confidence: 99%